A frequency control strategy for multimicrogrids with V2G based on the improved robust model predictive control. (1st May 2021) - Rao, Yingqing; Yang, Jun; Xiao, Jinxing; Xu, Bingyan; Liu, Wenjing; Li, Yonghui
Abstract: The microgrid contains many distributed power sources which have great randomness and volatility, so it is difficult to maintain the stable operation. As a mobile energy storage component with the capability of Vehicle-to-Grid (V2G), electric vehicles (EVs) provide a solution for the safe and stable operation of multimicrogrids. First, a microgrid system including micro gas turbines, distributed power and EVs which consider the random behavior of EV users as dynamic limitations is established. A coupled multimicrogrid system is then established. An improved robust model predictive frequency control strategy of multimicrogrids with EVs is proposed, and the whole control process is transformed into linear matrix inequalities (LMIs). A linear quadratic regulator (LQR) is added to further optimize control quantities to ensure the stability of the output. Finally, different scenarios are set up in the microgrids, and the simulation results are compared with other control methods. The simulation results show that the proposed control method can better suppress the frequency fluctuation with a faster response speed than other methods. The regulation of LQR is verified, and the proposed algorithm is shown to be effective in solving the uncertainty of system parameters. The establishment of multimicrogrids increases the anti-interference ability of the system. Highlights: A microgrid system including micro gas turbines, distributed power and EVs is established. A coupled multimicrogrid system is established. An improved robust model predictive frequency control strategy with a linear quadratic regulator (LQR) is proposed. The random behaviors and the travel demand of EV users are considered. The anti-interference ability of the multimicrogrids is increased.